Analisis Perbedaan Perilaku Konsumsi Belanja Online Berdasarkan Gender pada Mahasiswa FEBI UIN Banten - Bunga Ahista Rania; Hasan Bulqiah; Fatah Ghani Azkia; Wahyu Hidayat; Hadi Peristiwo; Fitri Fitri (Moneter : Jurnal Ekonomi dan Keuangan, 2024)
This research is not only to fulfill the author's final task, but also to find out if there are differences in online shopping consumption behavior between male and female students. The subjects in this study were active students of the Faculty of Economics and Islamic Business of UIN Sultan Maulana Hassanudin Banten semester 2-6 which was 26 people consisting of 11 men and 15 women. The data were collected through a licert scale questionnaire (1-5) and analyzed through the SPSS using the T-test Independes Test. The results of this study show that p = 0.916 (> 0.05) states that there is no significant difference in the consumption behavior of online shopping for male and female students at the Faculty of Economics and Islamic Business at UIN SMH Banten